Існування розв'язку та усереднення нелінійних багаточастотних задач із запізненням - Бігун, Я.Й. (Український математичний журнал, 2007)
We use the method of averaging over fast variables in studying multifrequency systems with linearly transformed argument. We prove the existence of solutions of initial and boundary-value problems in a small neighborhood of a solution of averaged problem. We obtain an estimate of error of the averaging method for slow variables.